Haplorchis taichui, Witenberg, 1930: Development of a HAT-RAPD marker for the detection of minute intestinal fluke infection - Chalobol Wongsawad (2018)
Specific primers to determine the presence of an intestinal fluke, Haplorchis taichui, were investigated using the high annealing temperature random amplified polymorphic DNA (HAT-RAPD) PCR, and 18 arbitrary primers (Operon Technologies), to generate different polymorphic DNA profiles. Thirteen kinds of parasites were used to compare fingerprints. A 256 bp HAT-RAPD marker, generated from the OPP-11 primer, was found to be H. taichui-specific, and this marker was cloned, transformed, and sequenced. From the sequence data, a pair of primers were designed with Genetyx-MAC ver.11 and indicated as: Hap-t F 5′-GGC CAA CGC AAT CGT CAT CC-3′ and Hap-t R 5′-GCG TCG GGT TTC AGA CAT GG-3′. These specific primers were tested for efficacy and specificity by amplifying them with all 13 parasites DNAs in PCR reaction. A 256 bp amplicon was generated, which was shown to have a positive result, only for H. taichui DNA. It revealed no cross-reaction with any of the other tested parasite species. The minimum DNA template, needed for detection by PCR, was 0.1 picogram (pg). The successful development of H. taichui-specific primers is expected to be beneficial for epidemiological studies and for prevention and control of these parasitic infections. © 2009 Elsevier Inc. All rights reserved.